Pengaruh transfer pricing terhadap agresivitas pajak perusahaan sektor energy yang terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Buntu, Hebenheiser; Kalangi , Lintje; Walandouw, Stanley Kho (Yayasan Widyantara Nawasena Raharja, 2025)
Tax aggressiveness refers to corporate tax planning activities that exploit loopholes in tax regulations to minimize tax obligations, either through legal means such as tax planning or illegal means like tax evasion. This practice has the potential to reduce a country's tax revenue. This study aims to examine the effect of transfer pricing on tax aggressiveness. The research population consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using a purposive sampling method, 28 companies were selected over four years, resulting in a total of 112 observations. This study employs a quantitative approach, utilizing simple linear regression to analyze the relationship between the independent and dependent variables. The findings indicate that transfer pricing does not significantly influence tax aggressiveness.